The Long Term Effects of Angiotensin Converting Enzyme Inhibition and Metabolic Control on Cardiovascular and Renal Outcomes in Hypertensive Type 2 Diabetic Patients - CHAN, Julien C. N. (Institutional Knowledge at Singapore Management University, 2000)
Long-term effects of angiotensin-converting enzyme inhibition and metabolic control in hypertensive type 2 diabetic patients. Background. In hypertensive type 2 diabetic patients, treatment with angiotensin-converting enzyme (ACE) inhibitors is associated with a lower incidence of cardiovascular events than those treated with calcium channel-blocking agents. However, the long-term renal effects of ACE inhibitors in these patients remain inconclusive. In 1989, we commenced a placebo-controlled, double-blind, randomized study to examine the anti-albuminuric effects of enalapril versus nifedipine (slow release) in 102 hypertensive, type 2 diabetic patients. These patients have been followed up for a mean trial duration of 5.5 ± 2.2 years. We examined the determinants, including the effect of ACE inhibition on clinical outcomes in these patients. Methods. After a six-week placebo-controlled, run-in period, 52 patients were randomized double-blind to receive nifedipine (slow release) and 50 patients to receive enalapril. After the one-year analysis, which confirmed the superior anti-albuminuric effects of enalapril (-54%) over nifedipine (+11%), all patients were continued on their previously assigned treatment with informed consent. They were subdivided into normoalbuminuric (N = 43), microalbuminuric (N = 34), and macroalbuminuric (N = 25) groups based on two of three 24-hour urinary albumin excretion (UAE) measurements during the run-in period. Renal function was shown by the 24-hour UAE, creatinine clearance (CCr), and the regression coefficient of the yearly plasma creatinine reciprocal (?-1/Cr). Clinical endpoints were defined as death, cardiovascular events, and/or renal events (need for renal replacement therapy or doubling of baseline plasma creatinine). Results. In the whole group, patients treated with enalapril were more likely to revert to being normoalbuminuric (23.8 vs. 15.4%), and fewer of them developed macroalbuminuria